Does gender affect the mathematics creativity of junior high school students?. (August 2020) - Permatasari, S D A; Budiyono,; Pratiwi, H
Abstract: Mathematics learning in the 21st century is a learning that emphasizes the importance of development in 4 aspects (4C), one of them is creativity. Mathematical creativity is students' skill to solve a problem with several strategies to reach different answers in certain tasks which are useful in developing mathematical reasoning. Relating to this context, nowadays, the issues of gender in education have been concern, that education must treat male and female students as equal. This research used one-way ANOVA to analyze the differences between the mathematical creativity between male and female students in junior high school. The research method used was quantitative descriptive. The sample of this research was 56 students of SMP Batik Surakarta who were taken by random sampling method. The results found that male and female students did not have differences in the ability of mathematical creativity. The insignificant difference can only be seen from their average scores. Female students are superior to male in the indicators of fluency, flexibility, and elaboration, but not in the indicator of originality.